2016
DOI: 10.1002/14651858.cd011025.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation for the treatment of epilepsy

Abstract: Overall, we judged the quality of evidence for the primary outcomes of this review to be low. There is evidence that rTMS is safe and not associated with any adverse events, but given the variability in technique and outcome reporting that prevented meta-analysis, the evidence for efficacy of rTMS for seizure reduction is still lacking despite reasonable evidence that it is effective at reducing epileptiform discharges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…A 2016 Cochrane review of available evidence for the use of TMS to reduce seizure frequency judged the quality to be low [97]. Fregni et al performed a randomized clinical trial of active or sham TMS in 21 patients with malformations of cortical development and refractory epilepsy [98].…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…A 2016 Cochrane review of available evidence for the use of TMS to reduce seizure frequency judged the quality to be low [97]. Fregni et al performed a randomized clinical trial of active or sham TMS in 21 patients with malformations of cortical development and refractory epilepsy [98].…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…The US FDA has approved neuromodulation devices which operate on the basis of deep brain stimulation (DBS), vagus nerve stimulation (VNS), and responsive neurostimulation (RNS) [9]. Other devices using transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) have been reported to provide noninvasive brain stimulation, but clinical trials have shown no benefit [13,14]. A primary limitation of TMS is that the inductive field decreases sharply and does not allow efficient energy deposition for subcortical stimulation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Low frequency repetitive rTMS (0.3-1 Hz) decreases cortical excitability, suggesting a potential therapeutic advantage for patients with drug-resistant epilepsy (Jan et al, 2017;Gersner et al, 2016). Chen et al (2016) retrospectively analyzed the evidence for the efficacy of TMS in drug-resistant epilepsy, evaluating studies that used rTMS of any frequency, duration, intensity and setup (focal or vertex treatment). Excruciatingly, the evidence for efficacy of rTMS for reduction in seizure rate/frequency is still lacking, due to the extreme variability in outcome reporting (Jan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%